The Determination of Sugars in Dairy Products: Development of a New Standard Method for the International Dairy Federation and the Internal Organization for Standardization. (22nd November 2019) - Sanders, Peter; Ernste-Nota, Veronica; Visser, Klaas; van Soest, Jeroen; Brunt, Kommer
Abstract: A method using high-performance anion-exchange chromatography (HPAEC) with a pulsed amperometric detector (PAD) for the determination of mono- and disaccharides is described. The method was accepted by theInternational Dairy Federation and the Internal Organization for Standardization as a new work item for the determination of sugars in dairy matrixes, and the Milk and Milk Products technical committee of ISO/TC 34/SC 5 accepted the topic "Milk and milkproducts – Determination of the sugar contents – High-performance anion-exchange chromatographic method (HPAEC–PAD)" as a new work item. The proposed method consists of an aqueous ethanol extraction of the sugars in the dairy sample, followed by clarification with Carrez I and II reagents. The clarified filtrate is diluted and then directly introduced in the HPAEC–PAD system forquantification of the sugars. A single-laboratory validation of the proposed method has been scheduled for spring 2017.